State-space representation of radiation forces in time-domain vessel models - Erlend Kristiansen; Åsmund Hjulstad; Olav Egeland (Modeling, Identification and Control, 2006)
The paper presents a method for generating a new and efficient time-domain formulation of the equations of motion for a vessel with frequency-dependent hydrodynamic coefficients. Previous work on this topic has relied on the use of convolution terms, whereas in this work state-space models are used. This leads to a model formulation that is well suited for controller design and simulation.